The Indians of Greater New York and the lower Hudson. Anthropological papers of the AMNH - Wissler, Clark.; Skinner, Alanson.; Finch, James K.; Bolton, Reginald Pelham.; Harrington, M. R. (Mark Raymond).; Schrabisch, Max.; Speck, Frank Gouldsmith. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1909)
xv, 242 p., [1] folded leaf of plates, [24] leaves of plates : ill., maps 24 cm. Includes bibliographical references and index. The Lenapé Indians of Staten Island / by Alanson Skinner -- Aboriginal remains on Manhattan Island / by James K. Finch -- The Indians of Washington Heights / by Reginald Pelham Bolton -- Archaeology of Manhattan Island / by Alanson Skinner -- The rock-shelters of Armonk, New York / by M.R. Harrington -- Indian rock-shelters in northern New Jersey and southern New York / by Max Schrabisch -- Ancient shell heaps near New York City / by M.R. Harrington -- Notes on the Mohegan and Niantic Indians / by F.G. Speck -- Archaeology of the New York coastal Algonkin / by Alanson Skinner.